Neonatal Respiratory Distress in Misan: Causes, Risk Factors, and Outcomes - Hussein Fadhil Musa Aljawadi; Esraa Abd Al-Muhsen Ali (Mashhad University of Medical Sciences, 2019)
Background: Respiratory distress is considered one of the most frequent causes of admission in the neonatal unit. Additionally, it is the leading cause of neonatal morbidity and mortality. This study aimed to determine the incidence of neonatal respiratory distress and its causes, risk factors, and outcomes to have a baseline data about the magnitude of respiratory distress with a further step toward the development of the neonatal field. Methods: This cross-sectional study was conducted in the neonatal care unit of Misan Hospital for Child and Maternity in Misan, Iraq, during one year. All the neonates who developed respiratory distress were included in this study according to the World Health Organization criteria. Results: The total number of neonatal admission during the study period was 870 cases among whom 738 (84.8%) subjects developed respiratory distress. The fatality rate was 21%, and the majority of deaths were found in respiratory distress syndrome (RDS) (67.1%). The RDS, transient tachypnea, and birth asphyxia were the major causes of neonatal respiratory distress. Statistically, prematurity, type of delivery, and number of babies at the delivery time were significantly associated with respiratory distress development. Conclusion: The incidence rate of neonatal respiratory distress was apparently high in Misan forming the most common cause of neonatal admission associated with a high mortality rate. Efforts toward preventing the causes and risk factors for neonatal respiratory distress, as well as, improving the efficacy of neonatal care unit are the significant challenges to improve the neonatal care and outcome.